Climatic Change of Summer Wind Direction and Its Impact on Hydrodynamic Circulation in the Pearl River Estuary - Bo Hong; Hanlu Xue; Liangsheng Zhu; Hongzhou Xu (Journal of Marine Science and Engineering, 2022)
Assessing the trend of sea surface wind is important for understanding the response of the marine environment to climate change. Analysis of wind data reveals that the summer wind direction in the Pearl River Estuary (PRE) shifts anticlockwise at a rate of −0.36°yr−1 over the past 42 years (1979–2020). The mean wind direction in July shifts from 183.6° (in 1979) to 169.3° (in 2020) and is predicted as 142.1° by 2100. How this long-term wind direction change affects the PRE hydrodynamic circulation structure has not been examined yet. A fully calibrated high resolution 3D hydrodynamic model is used to evaluate the response of local hydrodynamics to wind direction shifting in this study. The model results indicate that both the cross-channel wind-driven transport and along-channel seaward flow are weakened as wind direction shifts. Consequently, the lateral circulation is slowed down significantly while the longitudinal exchange flow is weakened slightly. A remarkable increase in stratification occurs in the coastal sea adjacent to the Modaomen where hypoxia has been frequently reported. The residence time of Lingding Bay increases slightly. The Momentum budget indicates the wind direction shifting can cause major changes in the barotropic pressure term, which is mainly balanced by the baroclinic pressure term and diffusion term.